Herbal medicine (Oryeongsan) for fluid and sodium balance in renal cortex of spontaneously hypertensive rats - You Mee Ahn; Hye Yoom Kim; Dae Gill Kang; Kyung Woo Cho; Ho Sub Lee (Integrative Medicine Research)
Background: Herbal medicine Oryeongsan (ORS), also known as Wulingsan in Chinese, has been used for the treatment of impaired body fluid balance. However, the mechanisms involved are not clearly defined. The purpose of the present study was to identify the actions of ORS on the renal excretory function and blood pressure (BP) and to define the mechanisms involved in association with renin-angiotensin system (RAS) and natriuretic peptide system (NPS) in spontaneously hypertensive rats (SHR), an animal model of human essential hypertension. Methods: Changes in urine volume (UV), excretion of electrolytes including Na+ (urinary excretion of Na+ (UNaV)) were measured. RT-PCR was performed to trace the changes in expression of RAS, NPS and sodium (Na+)-hydrogen (H+) exchanger 3 (NHE3) in the renal cortex. Results: In the SHR treated with vehicle (SHR-V) group, UV and UNaV were suppressed and the Na+ balance was maintained at the higher levels leading to an increase in BP compared to WKY-V group. These were accompanied by an increase in NHE3 expression with an accentuation of angiotensin I converting enzyme-angiotensin II type 1 (ACE-AT1) receptor and concurrent suppression of angiotensin II type 2 (AT2) receptor/ACE2-Mas receptor expression in the renal cortex. Chronic treatment with ORS increased UV and UNaV, and decreased the Na+ and water balance with a decrease in BP in the ORS-treated SHR-ORS group compared to SHR-V. These were accompanied by a decrease in NHE3 expression with a suppression of ACE-AT1 receptor and concurrent accentuation of AT2/ACE2-Mas receptor. Conclusion: The present study shows that ORS reduced BP with a decrease in Na+ and water retention by a suppression of NHE3 expression via modulation of RAS and NPS in SHR. The present study provides pharmacological rationale for the treatment of hypertension with ORS in SHR.